청소년을 위한 영양지수 개발과 타당도 검증 - 김혜영(Kim, Hye-Young); 이정숙(Lee, Jung-Sug); 황지윤(Hwang, Ji-Yun); 권세혁(Kwon, Sehyug); 정해랑(Chung, Hae Rang5); 곽동경(Kwak, Tong-Kyung); 강명희(Kang, Myung-Hee); 최영선(Choi, Young-Sun) (Journal of nutrition and health, 2017)
Purpose: The purpose of this study was to develop a nutrition quotient for adolescents (NQ-A) to assess overall dietary quality and food behavior of Korean adolescents. Methods: Development of the NQ-A was undertaken in three steps: item generation, item reduction, and validation. Candidate items of the NQ-A checklist were selected based on literature reviews, results of the fifth Korea National Health and Nutrition Examination Survey data, dietary guidelines for Korean adolescents, expert in-depth interviews, and national nutrition policies and recommendations. A total of 213 middle and high school students participated in a one-day dietary record survey and responded to 41 items in the food behavior checklist. Pearson's correlation coefficients between the responses to the checklist items along with nutritional status of the adolescents were calculated. Item reduction was performed, and 24 items were selected for the nation-wide survey. A total of 1,547 adolescents from 17 cities completed the checklist questionnaire. Exploratory factor and confirmatory factor analyses were performed to develop a final NQ-A model. Results: Nineteen items were finalized as the checklist items for the NQ-A. Checklist items were composed of five factors (balance, diversity, moderation, environment, and practice). The five-factor structure accounted for 47.2% of the total variance. Standardized path coefficients were used as weights of the items. The NQ-A and five-factor scores were calculated based on the obtained weights of the questionnaire items. Conclusion: Nutrition Quotient for adolescents (NQ-A) would be a useful instrument for evaluating dietary quality and food behavior of Korean adolescents. Further research on NQ-A is needed to reflect changes in adolescent's food behavior and environment. 본 연구는 생애주기별 영양지수 중 청소년을 위한 영양지수 (Nutrition Quotient for Adolescents, NQ-A) 모형을 개발하고자 수행되었다. 영양지수 평가항목 선정을 위해 식품섭취영역에서 20개 문항, 식행동 식습관 영역에서 21개 문항의 총 41개 문항으로 구성된 파일럿 조사용 체크리스트를 개발하였다. 청소년 213명을 대상으로 1일의 식사섭취실태 조사를 포함한 파일럿 조사를 수행하고, 체크리스트 항목 점수와 식사섭취실태 관련 변수들 간의 상관관계가 높은 24개의 평가항목으로 구성된 전국단위 조사용 체크리스트를 개발하였다. 전국단위 조사는 시도별 집락별로 층화추출된 중고등학생 1,547명에 대해 구조화된 설문지로 면대면 조사를 수행하였고, 탐색적 요인분석을 수행하여 청소년 영양지수의 평가 항목을 19개 항목의 5개요인으로 분류하고, 구조방정식 모형을 이용해 평가 항목의 구성타당도를 검증하고 추정된 경로계수를 가중치로 적용하였다. 청소년 영양지수를 위한 5개의 요인과 가중치는 각각 균형 0.25, 다양 0.15, 절제 0.25, 환경 0.15, 실천 0.20이었다. 균형 영역에는 과일 섭취 빈도, 흰 우유 섭취 빈도, 콩류 섭취 빈도, 생선 섭취 빈도의 4개 항목이 포함되었고, 다양 영역은 채소 반찬 섭취 빈도, 반찬 골고루 먹는 정도, 편식 정도의 3개 항목, 절제 영역은 과자 또는 달거나 기름진 빵 섭취 빈도, 가공 음료 섭취 빈도, 라면 섭취 빈도, 카페인 음료 섭취 빈도, 야식 섭취 빈도, 길거리 음식 섭취 빈도의 6개 항목, 환경 영역은 아침식사 빈도, 식탁에 앉아서 식사하는 정도, TV 핸드폰 컴퓨터 사용 시간의 3개 항목, 그리고 실천 영역은 영양 표시 확인 정도, 음식 먹기 전 손 씻는 정도, 운동 빈도의 3개 항목이 포함되었다. 전국단위 조사대상자의 영양지수 (NQ-A) 평균 점수는 56.0점이었고, 세부 영역별로는 균형 58.6점, 다양 55.6점, 절제 48.1점, 환경 70.6점, 실천 52.1점이었다. 영양지수 점수와 각 영역별 등급은 전국 조사 결과의 백분위수 분포를 기준으로 75~100 백분위의 경우 '상' 등급, 25 ~ <75 백분위의 경우 '중' 등급, 0 ~ <25 백분위는 '하' 등급으로 분류하였다. 영양지수의 경우 63.1~100점은 '상' 등급, 49.0~63점은 '중' 등급, 0~48.9점은 '하' 등급으로 판정되었다. 본 연구에서 개발된 청소년을 위한 영양지수는 19개 항목으로 구성된 식행동 체크리스트를 통해 영양지수 점수와 균형, 다양, 절제, 환경, 실천 영역의 점수를 산출할 수 있으며, 상대적인 NQ 등급 부여를 통해 식사의 질과 식행동이 양호한 지를 판정할 수 있다. 본 연구에서 개발된 청소년용 영양지수 (NQ-A)가 청소년의 식사의 질과 식행동 평가 및 영양교육의 효과 평가 등에 많이 활용될 것으로 기대된다.